Physiological and biomechanical responses induced by a continuous test and an intermittent test in middle-distance runners - Benhammou, S.; Clemente, F. M.; Mourot, L.; Belkadi, A. (International Journal of Sports Physiology and Performance, 2024)
Purpose: This study aimed to examine middle-distance runners` acute physiological and biomechanical responses to 2 maximal aerobic speed tests: an intermittent test (5 × 1 mintest) and a continuous test (University of Montreal Track Test [UM-TT]).